2020
DOI: 10.3390/ma13061427
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Gypsum-Based Materials Subjected to Thermal Load: Investigation of Reaction Mechanisms

Abstract: The thermal stability of gypsum-based materials, and in this context, especially their long-term behavior, is the background of our current research activities. A comprehensive investigation program was compiled in which detailed examinations of various model materials exposed to thermal loads were carried out. The understanding of the partly not entirely consistent state of knowledge shall be sharpened especially by in situ observations of the thermally induced conversion reaction of gypsum into hemihydrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…According to the graph, the first occurrence of mass loss occurred under the maximum temperature value of 43.65°C, probably related to a loss of free water still existing in the sample. The second mass loss event, occurred with a maximum of 138.55°C, most likely related to the loss of part of the crystallization water, these values detected in this analysis referring to the temperatures of partial dehydration of the gypsum with its consequent conversion to the form hemihydrate are in accordance with research reports related to the investigation of this type of ore published in the literature (Krause et al 2020;Ritterbach & Becker 2020). Some discrete events were perceived at temperatures above 450°C suggesting the presence of thermally active components, which were not detected by XRD analysis.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 91%
“…According to the graph, the first occurrence of mass loss occurred under the maximum temperature value of 43.65°C, probably related to a loss of free water still existing in the sample. The second mass loss event, occurred with a maximum of 138.55°C, most likely related to the loss of part of the crystallization water, these values detected in this analysis referring to the temperatures of partial dehydration of the gypsum with its consequent conversion to the form hemihydrate are in accordance with research reports related to the investigation of this type of ore published in the literature (Krause et al 2020;Ritterbach & Becker 2020). Some discrete events were perceived at temperatures above 450°C suggesting the presence of thermally active components, which were not detected by XRD analysis.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 91%
“…The pores in dental gypsum occur when air is trapped in the material during the mixing process, and pores form between crystals when the crystals of gypsum powder grow [ 31 ]. The pores of this dental gypsum can be identified as dark areas in scanning electron microscope images ( Figure 2 ) [ 32 ]. In this experiment, the plaster, which was a grade 2 gypsum, showed large spaces created by pores as dark areas during mixing, and some pores appeared as dark areas between the particles ( Figure 2 (a-1)).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data showed that the surface-bound crystalline, or structural, water remains intact even when the gypsum surface is in contact with aqueous solution. These results have important implications for bulk-surface exchange rates, solvation dynamics, and general reactivity at this ubiquitous mineral/aqueous interface …”
Section: Introductionmentioning
confidence: 92%
“…These results have important implications for bulksurface exchange rates, solvation dynamics, and general reactivity at this ubiquitous mineral/aqueous interface. 37 While AFM is a powerful tool for studying the overall waterinfluenced behavior of gypsum surfaces, this technique can only infer whether water is present and, if so, where. Simulations can suggest relative orientations, and the force curves resulting from AFM studies can be used to infer specific molecular−material interactions, but conclusions are necessarily indirect.…”
Section: ■ Introductionmentioning
confidence: 99%